Clinico‐Pathological Correlation in Progressive Ataxia and Palatal Tremor: A Novel Tauopathy. Issue 1 (April 2014) - Mari, Zoltan; Halls, Andrew J.M.; Vortmeyer, Alexander; Zhukareva, Victoria; Uryu, Kunihiro; Lee, Virginia M.‐Y.; Hallett, Mark
Abstract Palatal tremor (PT) is an uncommon movement disorder that has been subdivided into essential and symptomatic forms. A distinct subgroup of the symptomatic form presents with progressive ataxia and PT. The histopathology of progressive ataxia and PT has not been previously determined. This study consisted of a clinical review, histopathology, and electron microscopy of the brain of a man with progressive ataxia and PT. The inferior olivary hypertrophy was symmetrical and homogenous, and no focal pathologic lesions could be identified in the brainstem. Insoluble tau deposits were found in neurons, exclusively infratentorially. We present the clinical and pathological evaluation of a case of progressive ataxia and PT that provide evidence for a unique form of 4R tauopathy.